2022
DOI: 10.1093/eurheartj/ehac544.013
|View full text |Cite
|
Sign up to set email alerts
|

LA strain helps identifying the cardioembolic etiology of transient ischemic attacks

Abstract: Background Patients who have transient ischemic attacks (TIA) often suffer from asymptomatic and paroxysmal atrial fibrillation (AF). Due to the fact that AF is located in the atria, we sought to determine whether abnormalities in left atrial (LA) structure and function could help identify the cardioembolic cause of TIA in patients with sinus rhythm but with documented episodes of paroxysmal AF. Methods The research included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Atrial strain and 3D calculated volume have been shown to predict the development of AF, stroke and even heart failure in different scenarios, such as after a cerebrovascular event, after coronary artery bypass grafting and in dilated cardiomyopathy or hypertrophic cardiomyopathy. [22][23][24][25][26] In addition, atrial strain has shown prognostic value in a number of interventions, such as percutaneous mitral valve repair or aortic valve replacement. 6,22,26,27 The discovery of new therapies and the pathophysiological insights presented by numerous studies increasingly guide the need for the translation of cardiac imaging technology from research interests towards established measures of clinical practice, with a direct impact on our final objective: to provide the best possible care for our patients.…”
Section: Atrial Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…Atrial strain and 3D calculated volume have been shown to predict the development of AF, stroke and even heart failure in different scenarios, such as after a cerebrovascular event, after coronary artery bypass grafting and in dilated cardiomyopathy or hypertrophic cardiomyopathy. [22][23][24][25][26] In addition, atrial strain has shown prognostic value in a number of interventions, such as percutaneous mitral valve repair or aortic valve replacement. 6,22,26,27 The discovery of new therapies and the pathophysiological insights presented by numerous studies increasingly guide the need for the translation of cardiac imaging technology from research interests towards established measures of clinical practice, with a direct impact on our final objective: to provide the best possible care for our patients.…”
Section: Atrial Functionmentioning
confidence: 99%
“…[22][23][24][25][26] In addition, atrial strain has shown prognostic value in a number of interventions, such as percutaneous mitral valve repair or aortic valve replacement. 6,22,26,27 The discovery of new therapies and the pathophysiological insights presented by numerous studies increasingly guide the need for the translation of cardiac imaging technology from research interests towards established measures of clinical practice, with a direct impact on our final objective: to provide the best possible care for our patients.…”
Section: Atrial Functionmentioning
confidence: 99%
See 2 more Smart Citations